2011
DOI: 10.3758/s13423-011-0166-x
|View full text |Cite
|
Sign up to set email alerts
|

A perception theory in mind–body medicine: guided imagery and mindful meditation as cross-modal adaptation

Abstract: A new theory of mind-body interaction in healing is proposed based on considerations from the field of perception. It is suggested that the combined effect of visual imagery and mindful meditation on physical healing is simply another example of cross-modal adaptation in perception, much like adaptation to prism-displaced vision. It is argued that psychological interventions produce a conflict between the perceptual modalities of the immune system and vision (or touch), which leads to change in the immune syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 103 publications
(143 reference statements)
1
28
0
Order By: Relevance
“…We would advocate for greater systematic study of the construct of embodied imagery as one mechanism through which meditation practices are associated with increased well-being. Indeed whereas previous findings support the use of guided meditations in treating affective disorders, few studies have tried to unravel the intricacies regarding how individual differences in the capacity to vividly experience visual and embodied imagery relate to how much persons will enjoy and perceive themselves to benefit from guided meditation practices (Bedford, 2012;Kabat-Zinn, 2003, 2005. It has been suggested that the practice of embodiment meditations cultivates awareness of how our body, external environment and mind interact to create our sense of self (Kabat-Zinn, 2003, 2005 and, consistent with this sentiment, the current results support the use of meditations utilizing guided imagery as means to encourage the felt embodiment of positive selfreferential characteristics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We would advocate for greater systematic study of the construct of embodied imagery as one mechanism through which meditation practices are associated with increased well-being. Indeed whereas previous findings support the use of guided meditations in treating affective disorders, few studies have tried to unravel the intricacies regarding how individual differences in the capacity to vividly experience visual and embodied imagery relate to how much persons will enjoy and perceive themselves to benefit from guided meditation practices (Bedford, 2012;Kabat-Zinn, 2003, 2005. It has been suggested that the practice of embodiment meditations cultivates awareness of how our body, external environment and mind interact to create our sense of self (Kabat-Zinn, 2003, 2005 and, consistent with this sentiment, the current results support the use of meditations utilizing guided imagery as means to encourage the felt embodiment of positive selfreferential characteristics.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, it has been suggested that individual variability in the experienced vividness of imagery during guided meditations may be predicted by individual differences in mindfulness (Bedford, 2012). Mindfulness itself is generally described within the literature as a subjective state involving nonjudgmental awareness focused on the present moment (Bishop et al, 2004;Kabat-Zinn, 2003, 2005.…”
Section: Introductionmentioning
confidence: 98%
“…Although there is no clear explanation of how guided imagery brings about positive physical changes, one possible explanation has been provided by Bedford, who believes that perceptual processes are involved in imagery [32]. The combined effect of imagery on physical healing is simply another example of cross-modal adaptation in perception.…”
Section: Discussionmentioning
confidence: 99%
“…An attempt to translate grounded evidence in clinical practice has been introducedin a recent paper. Bedford (2012) theorizes that the visual component of perception can cure a number of medical symptoms by affecting the immune system. Vision, however, is controlled and modulated (Rizzolatti et al, 1994) by the motor system, as in the case of visual awareness studies demonstrating that the motor plan moderates perceptions of plan-congruent objects (Symes et al, 2008), or the reaching of a target in absence of visual awareness (Binsted et al, 2007).…”
Section: Resultsmentioning
confidence: 99%